The contribution of cell surface FcRn in monoclonal antibody serum uptake from the intestine in suckling rat pups - Cooper, Philip R.; Kliwinski, Connie M.; Perkinson, Robert A.; Ragwan, Edwin; Mabus, John R.; Powers, Gordon D.; Dorai, Haimanti; Giles-Komar, Jill; Hornby, Pamela J. (Frontiers in Pharmacology, 2014)
The neonatal Fc Receptor (FcRn) in intestinal epithelium is the primary mechanism for transfer of maternal immunoglobulin G (IgG) from suckled milk to serum; but the factors contributing to the rapid uptake of IgG are poorly understood. These studies help to determine the contribution of cell-surface FcRn in IgG uptake in 2-week old rat pups by varying local pH and binding conditions. Variants of a human wild-type IgG monoclonal antibody (mAb WT) were assessed for binding affinity (KD) to rat (r)FcRn at pH6.0 and subsequent off-rate at pH7.4 (1/s) by Surface Plasmon Resonance. Selected mAbs were administered intra-intestinally in isofluorane-anesthetized 2-week rat pups. Full-length mAb in serum was quantified by immunoassay, (r)FcRn mRNA expression by RT-PCR, and mAb epithelial localization was visualized by immunohistochemistry. After duodenal administration, serum levels of mAb variants correlated with their rFcRn off-rate at pH7.4, but not their affinity at pH6.0. The greatest serum levels of IgG were measured when mAb was administered in the duodenum where rFcRn mRNA expression is greatest, and was increased further by duodenal administration in pH6.0 buffer. More intense human IgG immunostaining was detected in epithelium than the same variant administered at higher pH. These data suggest an increased contribution for cell-surface receptor. We conclude that, in the neonate duodenum, receptor off-rates are as important as affinities for FcRn mediated uptake, and cell surface binding of IgG to rFcRn plays contributes to IgG uptake alongside pinocytosis; both of which responsible for increased IgG uptake.